PENERAPAN METODE PENGAJARAN BAHASA INGGRIS MIXED ENGLISH PROFICIENCY LEVELS: PERSEPSI GURU - Sri Gustiani; Tiur Simanjuntak; Risnawati Risnawati; Munaja Rahma (Aptekmas Jurnal Pengabdian pada Masyarakat, 2019)
This research is to know teachers’ perceptions on methods of teaching English for classes with mixed-English proficiency students: primary, elementary, intermediate, and advance levels.  These methods were some differentiated instructions taught in training to teachers of English as a community service activity which conducted to the teachers of English at Lembaga Bahasa (LB) Bagus Palembang. In this training, the participants learned the methods because they did not get the knowledge in their pre-service teacher training. They only had teaching methods for classes with one level of English proficiency. After they completed the training, they were monitored during the methods application in order to find their perceptions on teaching such class. The data were gathered via observations in the class during the monitoring. The observation data were, then, matched to the data from semi-structured interviews to know the participants’ perception on the methods in their classes.  The research revealed that the methods were proven to increase students’ participation in class with notification to high proficiency ones. However, it was not possible to suggest other best practices for dealing with all students in that class because not all practices work in a mixed-English proficiency class.